Subgingival microbiome of deep and shallow periodontal sites in patients with rheumatoid arthritis: a pilot study - Ryanne Lehenaff; Ryan Tamashiro; Marcelle M. Nascimento; Kyulim Lee; Renita Jenkins; Joan Whitlock; Eric C. Li; Gurjit Sidhu; Susanne Anderson; Ann Progulske-Fox; Michael R. Bubb; Edward K. L. Chan; et al. (BMC, 2021)
Abstract Background Subgingival microbiome in disease-associated subgingival sites is known to be dysbiotic and significantly altered. In patients with rheumatoid arthritis (RA), the extent of dysbiosis in disease- and health-associated subgingival sites is not clear. Methods 8 RA and 10 non-RA subjects were recruited for this pilot study. All subjects received full oral examination and underwent collection of subgingival plaque samples from both shallow (periodontal health-associated, probing depth ≤ 3mm) and deep subgingival sites (periodontal disease-associated, probing depth ≥ 4 mm). RA subjects also had rheumatological evaluation. Plaque community profiles were analyzed using 16 S rRNA sequencing. Results The phylogenetic diversity of microbial communities in both RA and non-RA controls was significantly higher in deep subgingival sites compared to shallow sites (p = 0.022), and the overall subgingival microbiome clustered primarily according to probing depth (i.e. shallow versus deep sites), and not separated by RA status. While a large number of differentially abundant taxa and gene functions was observed between deep and shallow sites as expected in non-RA controls, we found very few differentially abundant taxa and gene functions between deep and shallow sites in RA subjects. In addition, compared to non-RA controls, the UniFrac distances between deep and shallow sites in RA subjects were smaller, suggesting increased similarity between deep and shallow subgingival microbiome in RA. Streptococcus parasanguinis and Actinomyces meyeri were overabundant in RA subjects, while Gemella morbillorum, Kingella denitrificans, Prevotella melaninogenica and Leptotrichia spp. were more abundant in non-RA subjects. Conclusions The aggregate subgingival microbiome was not significantly different between individuals with and without rheumatoid arthritis. Although the differences in the overall subgingival microbiome was driven primarily by probing depth, in contrast to the substantial microbiome differences typically seen between deep and shallow sites in non-RA patients, the microbiome of deep and shallow sites in RA patients were more similar to each other. These results suggest that factors associated with RA may modulate the ecology of subgingival microbiome and its relationship to periodontal disease, the basis of which remains unknown but warrants further investigation.